NUOVA OFFICINA ASSERGI: a novel infrastructure for the production of cryogenic and radiopure Si-based photodetectors - Consiglio, L.; Flammini, A.; Ianni, A.; Marasciulli, A.; Panella, G.; Pietrofaccia, L.; Sablone, D.; Tartaglia, R. (Frontiers in Physics, 2024)
The NUOVA OFFICINA ASSERGI (NOA), is a new facility for the production and integration of large area Silicon photo-detectors operating at cryogenic temperatures. Silicon Photo Multipliers are demonstrating to be a promising technology for next generation experiments searching for rare events in underground laboratories. New photosensor technology with high performance at cryogenic temperature has been developed by Fondazione Bruno Kessler (FBK) and integrated at Laboratori Nazionali del Gran Sasso (LNGS) in large area optical units, thus opening the frontiers toward the realization of scalable liquid Argon experiments probing Dark Matter. The massive production of such detectors is now feasible in NOA, a clean room of 421 m 2 designed to be operated in Radon-free mode commissioned and operational at LNGS, hosting the most advanced packaging machines and electronic test facilities for the integration of Silicon devices in a dust controlled environment. The infrastructure layout is splitted into two experimental areas both for the production of electronic devices and cryogenic temperature test and for operating with large detector installation. The NOA facility can be operated with a Radon abatement system becoming in perspective a unique facility for the packaging and testing of SiPM based photosensors and for assembling of detectors components in a Radon-free environment. Therefore, NOA is an infrastructure to support the deployment of underground experiments at LNGS and the developments of new technologies for the search of rare events such as dark matter and neutrinoless double-beta decay.